Application of Problem Based Learning in Grade 3 Islamic Religious Education Lessons on Disgraceful Morals in Elementary Schools: Penerapan Problem Based Learning dalam Pelajaran Pendidikan Agama Islam Kelas 3 Materi Akhlak Tercela di Sekolah Dasar - Alfia, Shadita; Nadlif, Ainun (Indonesian Journal of Education Methods Development, 2023)
This study aims to determine how the application of problem based learning and to find out the advantages and disadvantages of problem based learning learning models for Islamic Religious Education class 3 material on despicable morals at Karangbong State Elementary School. This research is a descriptive qualitative research by understanding the phenomenon of what is experienced by the research subject. In this study, the subjects of the study were grade 3 students at Karangbong State Elementary School, Islamic Religious Education teachers, and Administration teachers. The location of this research was conducted at Karangbong State Elementary School. The data collection technique uses Miles and Huberman which consists of four components of analysis, namely, data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that the application of the problem-based learning model in Islamic Religious Education class 3 material on reprehensible morals is in accordance with the steps, and students do not experience difficulties in applying the model. By using this model, students become more active and think critically. The only drawback is time.